2017
DOI: 10.5539/cco.v6n2p19
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Expression of Hypoxanthine Guanine Phosphoribosyltransferase within Malignant Tissue

Abstract: Hypoxanthine Guanine Phosphoribosyltransferase (HPRT) is a housekeeping enzyme involved in the purine synthesis of guanine and inosine in the salvage pathway. While other salvage pathway enzymes, such as TK1, have been established as biomarkers for both cancer cell proliferation and cancer development, little research been done to evaluate whether HPRT has the same potential as a cancer biomarker. We designed this study to determine if HPRT has value as an identifier of malignancy within the most common types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Müller et al [ 158 ] using quantitative PCR, found that HPRT was detectable in cultured human MDA-MB-231 breast carcinoma cells, primary tumors, and tumor-infiltrated lungs of SCID-mice injected with human MDA-MB-231 breast carcinoma cells, but undetectable in normal mouse lungs, and that the human HPRT mRNA content in lungs of mice correlated with the size of the tumor. More recently, using immunohistochemistry staining, the level of HPRT has been evaluated in normal and malignant tissues from human lung, breast, colon and prostate [ 159 ]. Although a significant variability within patients with regard to the relative expression of HPRT both in normal and malignant tissues has been observed, an overall trend showing upregulation of HPRT in cancerous tissues has been reported.…”
Section: Hypoxanthine-guanine Phosphoribosyltransferase (Hprt)mentioning
confidence: 99%
See 1 more Smart Citation
“…Müller et al [ 158 ] using quantitative PCR, found that HPRT was detectable in cultured human MDA-MB-231 breast carcinoma cells, primary tumors, and tumor-infiltrated lungs of SCID-mice injected with human MDA-MB-231 breast carcinoma cells, but undetectable in normal mouse lungs, and that the human HPRT mRNA content in lungs of mice correlated with the size of the tumor. More recently, using immunohistochemistry staining, the level of HPRT has been evaluated in normal and malignant tissues from human lung, breast, colon and prostate [ 159 ]. Although a significant variability within patients with regard to the relative expression of HPRT both in normal and malignant tissues has been observed, an overall trend showing upregulation of HPRT in cancerous tissues has been reported.…”
Section: Hypoxanthine-guanine Phosphoribosyltransferase (Hprt)mentioning
confidence: 99%
“…Although a significant variability within patients with regard to the relative expression of HPRT both in normal and malignant tissues has been observed, an overall trend showing upregulation of HPRT in cancerous tissues has been reported. With the exception of lung cancer, the authors claim that the upregulation of HPRT is independent of cancer grade or stage, and they hypothesize that HPRT could be utilized as an early biomarker because it appears to be upregulated in cancer regardless of stage [ 159 ]. A surface expression of HPRT has been reported in lung cancer cell lines, although the reason for this external presentation is presently unknown [ 160 ].…”
Section: Hypoxanthine-guanine Phosphoribosyltransferase (Hprt)mentioning
confidence: 99%
“…Cell lysates were blotted for GAPDH, B2M, EEF2, and HPRT expression utilizing standard Western Blotting techniques described in Sewda et al, with minor modifications. 22 Briefly, each sample was boiled for 5 minutes prior to running on a 12% polyacrylamide gel under reducing conditions. Gels were then transferred to a nitrocellulose membrane (Biorad Laboratories Hercules, CA, USA), blocked, and treated with primary antibody (1:1000 dilution) overnight at 4°C on a shaker.…”
Section: Western Blot and Quantificationmentioning
confidence: 99%
“…20 In addition, further evidence shows that HPRT demonstrates significant variability between normal patients and those with cancer. 21,22 The inconsistency present in the literature is concerning as HPRT is widely used to standardize both RNA and protein levels.…”
Section: Introductionmentioning
confidence: 99%
“…The protein is a housekeeping protein that is found within all normal somatic cells in low levels [ 336 ]. There is an upregulation of HPRT1 in certain cancer types, making it a promising biomarker for the treatment of these cancers [ 337 , 338 ]. In addition, the protein has also been shown to have significant surface localization on certain malignancies such as lung and colorectal cancer [ 339 , 340 ].…”
Section: Up and Coming Biomarkersmentioning
confidence: 99%